Heterozygous Tsc2 (Tsc2+/–) mouse model to study induced renal cancer in response to ionizing radiation at low doses. (2nd December 2018) - M A, Sureshkumar; Delma, Caroline R; Manickam, Krishnan; Mohan, Sumathy; Habib, Samy L; Natarajan, Mohan
Abstract: Kidneys are one of the main dose-limiting organs in radiotherapeutic procedures of lower abdomen. Likewise, the threat of exposure of radiosensitive organs such as kidneys in warfare or radiation accidents among military personal or due to terrorist activities in general public is of increasing concern. These events warrant the need for appropriate animal models to study the acute and chronic effects of low- and high-dose rate radiation exposures. In this study, for the first time, we validated Tsc2 +/– mouse model to study whether radiation accelerates carcinogenesis in kidneys. Tsc2 +/– mice at increasing age groups at 8 and 10 months were exposed to repeated doses of gamma radiation (0.4 Gy × 5) and assessed for aggravated kidney tumor formation at 2 months post-irradiation. Animals from irradiated group showed a significant increase in numbers of bilateral, multifocal tumors compared with mock-irradiated animals. Intra-glomerular reactive oxygen species (ROS) levels measured by dihydroethidium florescence showed significant increases in ROS production in irradiated Tsc2 +/– mice compared with non-irradiated animals. Similarly, selective hematological parameters and glomerular filtration rate were further reduced significantly in irradiated Tsc2 +/– mice. Tsc2 protein, tuberin in irradiated mice, however, remains at the same reduced levels as that of the mock-irradiated heterozygous Tsc2 mice. The results indicate that radiation alters kidney homeostatic function and influences high spontaneous incidence of renal cell carcinoma in this rodent model. Repurposing of Tsc2 +/– mice model will, therefore, provide a unique opportunity to study acute and delayed effects of radiation in the development of kidney cancers. Abstract : The article implies the significance of repurposing tuberous sclerosis complex heterozygous animal model to understand accelerated progression of kidney cancer in response to radiation. The findings will have major impact on patients undergoing radiotherapy or in whole-body exposure during radiation catastrophes.